'Welcome to London': Spectral Spaces in Sherlock Holmes's Metropolis - Lee, Christina (University of Technology, Sydney - ePress, 2014)
This article examines the burgeoning tourist trade for locations featured in fictional narratives in popular culture. Symptomatic of a postmodern, hyperlinked culture referencing a vast reservoir of texts, such tourism produces a convergence of effects which render places ambivalent. Through a case study of Sherlock Holmes tourism in London, I argue that the city is constructed as seething with the spectral in which there is tension and slippage between paratexts, past and present, history and fiction, the observable and imperceptible. The tourist seeks out embodied experiences of their own secret London(s) which reside somewhere in-between the multiplicitous topographies.